1983
DOI: 10.1007/bf01075262
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of short- and long-chain acylarnitine by etio-chloroplasts of greening barley leaves

Abstract: Etio-chloroplasts of barley, purified on sucrose density gradients were shown to possess carnitine long-chain acyltransferase (carnitine palmitoyltransferase, EC 2.3.1.21) activity and carnitine short-chain acyltransferase (carnitine acetyltransferase EC 2.3.1.7) activity. These enzymes may play a role in the transport of acyl groups as acylcarnitines through the membrane barrier of barley etio-chloroplasts and also 'or alternatively' may spare CoA by transferring short- and long-chain acyl groups from short-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Recent evidence indicates that free fatty acids are quickly transported to the cytosol in the form of acyl-CoAs due to the action of an acyl-CoA synthetase located in the outer plastidial membrane (Koo et al 2004). This export model involving free fatty acid intermediates created certain controversy when it was Wrst hypothesized, and alternative models suggest that acyl-CoA or acyl-carnitine derivatives are exported instead (Joyard and Stumpf 1980;Thomas et al 1983;McLaren et al 1985). However, 18 O labeling experiments demonstrated that unesteriWed acyl moieties were indeed released during the fatty acid biosynthesis in plants (Pollard and Ohlrogge 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Recent evidence indicates that free fatty acids are quickly transported to the cytosol in the form of acyl-CoAs due to the action of an acyl-CoA synthetase located in the outer plastidial membrane (Koo et al 2004). This export model involving free fatty acid intermediates created certain controversy when it was Wrst hypothesized, and alternative models suggest that acyl-CoA or acyl-carnitine derivatives are exported instead (Joyard and Stumpf 1980;Thomas et al 1983;McLaren et al 1985). However, 18 O labeling experiments demonstrated that unesteriWed acyl moieties were indeed released during the fatty acid biosynthesis in plants (Pollard and Ohlrogge 1999).…”
Section: Introductionmentioning
confidence: 94%
“…The free fatty acids released by thioesterases are only detected at very low levels in developing seeds, as they are rapidly converted to their corresponding acyl‐CoAs by long chain acyl‐CoA synthetases (LACSs, EC 6.2.1.3; Schnurr et al ). Although initially controversial (Thomas et al , ), the existence of free fatty acids as intermediates of fatty acid synthesis was confirmed in labeling experiments (Pollard and Ohlrogge ).…”
Section: Introductionmentioning
confidence: 98%
“…Although initially controversial (Thomas et al 1982(Thomas et al , 1983, the existence of free fatty acids as intermediates of fatty acid synthesis was confirmed in labeling experiments (Pollard and Ohlrogge 1999).…”
mentioning
confidence: 98%
“…[3]). Enzymatic activities related to carnitine transfer on acyl moieties have also been measured in plant tissues and localised in mitochondria [4,5] and plastids [6,7]. The recent identification and characterisation of an Arabidopsis thaliana knockout mutant for a putative carnitine transmembrane carrier (BOU) suggest that carnitine may have a much more critical role than expected [8].…”
Section: Introductionmentioning
confidence: 98%